MENINGKATKAN HASIL BELAJAR IPA MELALUI MODEL PROBLEM BASED LEARNING PADA KELAS V DI SDN KEBON BARU 09 JAKARTA SELATAN - Salsa Sabrina; Endang Wahyudiana; Engga Dallion (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to enhance students’ achievement in Science learning through the implementation of the Problem Based Learning (PBL) model in class V-C of SDN Kebon Baru 09, South Jakarta, consisting of 30 students. The research employed a Classroom Action Research (CAR) design with data collected through observation using teacher and student activity monitoring sheets, learning achievement tests, and documentation. The findings revealed that the application of the Problem Based Learning model improved students’ achievement in Science. In the first cycle, the mastery learning percentage reached 50%, while in the second cycle it increased to 83%, showing an improvement of 33%. Therefore, it can be concluded that the use of the Problem Based Learning model is effective in improving Science learning achievement among fifth-grade students at SDN Kebon Baru 09, South Jakarta.